2005
DOI: 10.1007/s10450-005-4909-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of ZSM-12 Zeolite with Different Si/Al Ratio

Abstract: In this work the acid properties of a series of HZSM-12 zeolites with different Si/Al ratio were studied. The ZSM-12 crystals were synthesized by the hydrothermal method starting from a gel with the following molar composition: 20MTEA:10Na 2 O:x Al 2 O 3 :100SiO 2 :2000H 2 O, with x = 0.50, 0.67, 1, 1.25 and 2, respectively. The gels were crystallized at 140 • C for 6 days, then washed, dried and calcined to remove the MTEA template. The samples were ion-exchanged with an ammonium chloride solution and calcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…It can be seen that in the first stage of mass loss for these three samples there was a reduction of about 11% of mass, corresponding to the desorption of the intracrystalline water contained in the sample. Similar to results showed by 11 , the second stage of mass loss may correspond to the decomposing MTEA + ions present in the zeolite pores. However, the third step can be characterized as the coke removing and residual amines decomposition formed from Figure 4 (a, b, c) show the mass loss of not calcined samples impregnated with different titanium contents.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It can be seen that in the first stage of mass loss for these three samples there was a reduction of about 11% of mass, corresponding to the desorption of the intracrystalline water contained in the sample. Similar to results showed by 11 , the second stage of mass loss may correspond to the decomposing MTEA + ions present in the zeolite pores. However, the third step can be characterized as the coke removing and residual amines decomposition formed from Figure 4 (a, b, c) show the mass loss of not calcined samples impregnated with different titanium contents.…”
Section: Resultssupporting
confidence: 81%
“…Mass loss of not calcined zeolite ZSM-12 is characterized by three steps 11 : (I) Desorption of intracrystalline water, (II) decomposition of MTEA + ions located inside the zeolite ZSM-12 pores; (III) decomposition of MTEA + cations strongly bound to the surface. Figure 3 (a, b, c) show the mass loss of not calcined samples X6, Y6 and W6.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images provide the first evidence of the inclusion of Al into the zeolite framework. It is well-known that the crystallinity of the high-silica zeolites drops rapidly with the presence of aluminum in the reaction mixture [16]. In our case the crystal grains of Al-containing products are much smaller in comparison with the puresilica product (Fig.…”
Section: Synthesismentioning
confidence: 44%
“…Ar ange of optimum synthesis parameters for synthesizing Nano-MTW were determined by evaluating the effects of initial SiO 2 /Al 2 O 3 ratio and alkalinity of the synthetic gel on crystalline phase and morphologyo ft he final products.T he XRD results confirmed that pure MTW zeolite phase was successfully generated in ac ertain SiO 2 /Al 2 O 3 ratio around 40 ( Figure S4), similar to the synthesis of pure ZSM-12 using TEAOH or TEABr as a template. [42] As indicated by XRD patterns,ahigh SiO 2 /Al 2 O 3 ratio ( % 80) led to the formation of magadiite phase, and SiO 2 / Al 2 O 3 ratio around 60 resulted in the existence of mordenite (MOR) impurity phase. If the SiO 2 /Al 2 O 3 ratio was lower than 20, the MTW phasew as completely missing and accompanied by cristobalite phase and zeolite P. [43] Actually,e xcessive silicon sourcesp referentially formed silicate under alkaline conditions, whereas relatively low ratio of silicon species limited the formation of high silicon MTW zeolite.…”
Section: Characterizationr Esultsmentioning
confidence: 98%
“…As shown in Figure S6, only amorphous products were detected at low Na 2 O/SiO 2 ratios (< 0.075), possibly because low alkalinity of the system restricted the solubility of the silicon source and consequently retarded the crystallization rate. [42] At the Na 2 O/SiO 2 ratio around 0.124, pure MTW zeolite was obtained ( Figure S6 b). However,a th igher Na 2 O/ SiO 2 ratio (> 0.223), an MOR impurity phase was detected,a nd then it became the major product at Na 2 O/SiO 2 ratio of 0.323 ( Figure S7 c, Figure S6 d).…”
Section: Characterizationr Esultsmentioning
confidence: 99%